In-Silico Analysis of Differentially Expressed Genes and Their Regulating microRNA Involved in Lymph Node Metastasis in Invasive Breast Carcinoma. (2nd January 2022) - Modi, Anupama; Purohit, Purvi; Gadwal, Ashita; Ukey, Shweta; Roy, Dipayan; Fernandes, Sujoy; Banerjee, Mithu
Abstract: Axillary nodal metastasis is related to poor prognosis in breast cancer (BC). Key candidate genes in BC lymph node metastasis have been identified from Gene Expression Omnibus datasets and explored through functional enrichment database for annotation, visualization and integrated discovery (DAVID), protein-protein interaction by Search Tool for the Retrieval of Interacting Genes and proteins (STRING), network visualization (Cytoscape), survival analysis (GEPIA, KM Plotter), and target prediction (miRNet). A total of 102 overlapping differentially expressed genes were found. In-silico survival and expression analyses revealed six candidate hub genes, Desmocollin 3 (DSC3), KRT5, KRT6B, KRT17, KRT81, and SERPINB5, to be significantly associated with nodal metastasis and overall survival, and 83 MicroRNA (miRNAs), which may be potential diagnostic markers and therapeutic targets in BC patients.